In silico/computational analysis of mevalonate pyrophosphate decarboxylase gene families in Campanulids - Cui Minghui (De Gruyter, 2021)
Mevalonate pyrophosphate decarboxylase (MPD) is a key enzyme in terpenoid biosynthesis. MPD plays an important role in the upstream regulation of secondary plant metabolism. However, studies on the MPD gene are relatively very few despite its importance in plant metabolism. Currently, no systematic analysis has been conducted on the MPD gene in plants under the order Apiales, which comprises important medicinal plants such as Panax ginseng and Panax notoginseng. This study sought to explore the structural characteristics of the MPD gene and the effect of adaptive evolution on the gene by comparing and analyzing MPD gene sequences of different campanulids species. For that, phylogenetic and adaptive evolution analyses were carried out using sequences for 11 Campanulids species. MPD sequence characteristics of each species were then analyzed, and the collinearity analysis of the genes was performed. As a result, a total of 21 MPD proteins were identified in 11 Campanulids species through BLAST analysis. Phylogenetic analysis, physical and chemical properties prediction, gene family analysis, and gene structure prediction showed that the MPD gene has undergone purifying selection and exhibited highly conserved structure. Analysis of physicochemical properties further showed that the MPD protein was a hydrophilic protein without a transmembrane region. Moreover, collinearity analysis in Apiales showed that MPD gene on chromosome 2 of D. carota and chromosome 1 of C. sativum were collinear. The findings showed that MPD gene is highly conserved. This may be a common characteristic of all essential enzymes in the biosynthesis pathways of medicinal plants. Notably, MPD gene is significantly affected by environmental factors which subsequently modulate its expression. The current study’s findings provide a basis for follow-up studies on MPD gene and key enzymes in other medicinal plants.